Analisis Faktor Risiko Perilaku Cuci Tangan dan Konsumsi Jajanan terhadap Kejadian Kecacingan pada Siswa SD X - Sulastina, Nur Afni; Fitri, Melly; Oktaviana Hasibuan, Tri (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2025)
Background: Soil-transmitted helminth (STH) infections remain a common health problem among school-aged children, particularly those related to poor hygiene practices and the consumption of unhygienic snacks. Handwashing habits and choosing clean food play an essential role in preventing the fecal–oral transmission of helminths. This study aimed to analyze the relationship between gender, handwashing behavior, and snack consumption with the occurrence of helminth infections among students at SD X. Method: This research employed a descriptive-analytic design with a cross-sectional approach. A total sample of 31 students was selected using a total sampling technique. Data were collected through questionnaires and stool examinations. The data were analyzed using univariate and bivariate analyses with the Chi-square test. Results: The results showed that 25.8% of the students were infected with helminths. Based on gender, the proportion of infection was equal among male and female students, with a Chi-square test result of p = 0.731. Students with poor handwashing practices showed a higher proportion of helminth infections; however, the association was not statistically significant (p = 0.073). Similarly, students who frequently consumed unhygienic snacks had a higher infection rate, yet no significant relationship was found (p = 0.314). Conclusion: In conclusion, there was no significant association between gender, handwashing behavior, and snack consumption with helminth infections among students of SD X. Nevertheless, the observed tendencies suggest that poor hygiene behavior and the consumption of unhygienic snacks may contribute to an increased risk of helminth infection. Keywords: Handwashing Behavior, Snack Consumption, Incidence of Helminth Infection